Nghiên cứu địa y học môi trường ở làng nghề cơ khí Nam Giang tỉnh Nam Định - Lài, Lê Thị; Below, H.; Eidam, J.; Kasbohm, J.; Kramer, A. (Vietnam Journal of Earth Sciences, 2001)
An environmental and geomedical study in the craft oriented vilage Nam Giang, province Nam Dinh